2005
DOI: 10.1650/7808
|View full text |Cite
|
Sign up to set email alerts
|

Stopover Ecology of Autumn Landbird Migrants in the Boise Foothills of Southwestern Idaho

Abstract: Published as "Stopover Ecology of Autumn Landbird Migrants in the Boise Foothills of Southwestern Idaho" in The Condor 107(2):244-258. © 2005 by the Regents of the University of California. Copying and permissions notice: Authorization to copy this content beyond fair use (as specified in Sections 107 and 108 of the U. S. Copyright Law) for internal or personal use, or the internal or personal use of specific clients, is granted by the Regents of the University of California for libraries and other users, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…Both Carlisle et al (2004) and DeLong et al (2005) discussed the possibility that montane woodlands in and around the Great Basin may provide cooler microclimates and higher food availability during late summer and early autumn than surrounding lowlands and thus provide more favorable habitat to migrants at those times of year and Patten et al (2003) suggested the same pattern for the Sonoran Desert. In fact, Carlisle (2005) found that whereas arthropod and fruit availability at an autumn stopover site in southwestern Idaho differed significantly among years, most migrant species were able to gain mass in each year, indicating the presence of adequate food sources for re-fueling at this montane site. Recently, Wightman et al (2007) showed that ponderosa pine forests with a deciduous component were also important for autumn migrants.…”
Section: Habitat Associations Of Migrantsmentioning
confidence: 91%
See 3 more Smart Citations
“…Both Carlisle et al (2004) and DeLong et al (2005) discussed the possibility that montane woodlands in and around the Great Basin may provide cooler microclimates and higher food availability during late summer and early autumn than surrounding lowlands and thus provide more favorable habitat to migrants at those times of year and Patten et al (2003) suggested the same pattern for the Sonoran Desert. In fact, Carlisle (2005) found that whereas arthropod and fruit availability at an autumn stopover site in southwestern Idaho differed significantly among years, most migrant species were able to gain mass in each year, indicating the presence of adequate food sources for re-fueling at this montane site. Recently, Wightman et al (2007) showed that ponderosa pine forests with a deciduous component were also important for autumn migrants.…”
Section: Habitat Associations Of Migrantsmentioning
confidence: 91%
“…In particular, applications of established techniques (mist-netting and associated analyses) to previously unstudied areas, and use of an important and novel technique (plasma metabolite sampling), have contributed to a growing body of literature pertaining to stopover ecology and habitat suitability (Wang et al 1998, Kelly et al 2002a, Cerasale 2004, Carlisle et al 2005b, Guglielmo et al 2005, Paxton et al 2007b.…”
Section: Stopover Ecology and Energetic Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each method of counting, capture of landbirds in mist nets and counts of raptors, is widely recognized as valid for monitoring avian migration. Unlike raptor counts, however, landbirdcapture data are not a measure of birds actually migrating at the time of observation, and Lucky Peak is a productive stopover point (Carlisle et al 2005). Though our primary goal is to study birds during their migration, not all birds caught on a given day have necessarily been migrating that day or the night before, evidenced by the fact that up to 15% of individual birds are recaptured up to several days after initial capture (Carlisle et al 2005).…”
Section: Assumptions and Potential Limitations Of The Datamentioning
confidence: 99%